Biologics targeting IL-17 sharply reduce circulating T follicular helper and T peripheral helper cell sub-populations in psoriasis - Tsiogkas, Sotirios G.; Mavropoulos, Athanasios; Dardiotis, Efthimios; Zafiriou, Efterpi; Bogdanos, Dimitrios P. (Frontiers in Immunology, 2024)
Introduction Circulating T follicular helper (cTfh) cells and circulating T peripheral helper (cTph) cells (which share common characteristics with the cTfh population) are implicated in the pathogenesis of immune-mediated and autoimmune diseases such as psoriasis (Ps). Their close interplay with the interleukin 17 (IL-17) axis and the ex vivo effect of IL-17-targeting biologic agents used to treat Ps on them are elusive. This study aimed to investigate the effect of biologics targeting IL-17 on cTfh and cTph cell subpopulations isolated from the blood of patients with Ps. Methods Peripheral blood mononuclear cells (PBMCs) were isolated from patients with Ps at treatment initiation and three months later. Samples were also collected from controls. Cells were stained using monoclonal antibodies. Flow cytometry assessed the fraction of cTfh (CD3+CD4+CXCR5+) and cTph (CD3+CD4+CXCR5-PD-1hi) cells.. Results Flow cytometric analysis showed increased fractions of activated cTfh subsets including ICOS+ and ICOS+PD-1+ expressing cells, in patients compared to controls. Biologic blocking of IL-17A diminished the cTfh population. Furthermore, ICOS+ and ICOS+PD-1+ sub-populations were also inhibited. Finally, the cTph cell fraction significantly decreased after three months of successful treatment with biologics. Conclusion Early anti-IL-17-mediated clinical remission in Ps is associated with decreased cTfh and cTph cell subpopulations.